COVID testing hesitancy among pregnant patients: lessons learned from the COVID-19 pandemic about the unique needs and challenges of medically complex populations - Ruth M. Farrell; Caitlin Dahler; Rachel Pope; Ellen Divoky; Christina Collart (BMC, 2024)
Abstract Background Pregnant patients were a significant population to consider during the pandemic, given the impact of SARS-CoV-2 infection on obstetric outcomes. While COVID testing was a central pillar of infection control, it became apparent that a subset of the population declined to test. At the same time, data emerged about pregnant persons also declining testing. Yet, it was unknown why pregnant patients declined tests and if those reasons were similar or different from those of the general population. We conducted this study to explore pregnant patients' attitudes, access, and utilization of COVID-19 testing to support healthcare for infection prevention management for this unique and medically complex population. Methods We conducted a qualitative study of patients who were currently or recently pregnant during the early stages of the pandemic and received outpatient prenatal care at one of the participating study sites. An interview guide was used to conduct in-depth telephone interviews. Coding was performed using NVivo, and analysis was conducted using Grounded Theory. Results The average age of the participants (N = 37) was 32 (SD 4.21) years. Most were < 35 years of age (57%) and self-described as White (68%). Qualitative analysis identified themes related to barriers to COVID-19 testing access and use during pregnancy, including concerns about test accuracy, exposure to COVID-19 in testing facilities, isolation and separation during labor and delivery, and diminished healthcare quality and patient experience. Conclusions The implementation of widespread and universal COVID testing policies did not address the unique needs and challenges of pregnant patients as a medically complex population. It is important to understand the reasons and implications for pregnant patients who declined COVID testing during the current pandemic to inform strategies to prevent infection spread in future public health emergencies.